SUPERVISION OF GOODS AND SERVICES PROCUREMENT DURING THE COVID-19 PANDEMIC BY THE GOVERNMENT’S INTERNAL SUPERVISORY APPARATUS (APIP) - Amrie Firmansyah; Friska Dwi Enita; Ramadhan Try Adriansyah; Reza Ardian Putra Dewantara (IPSAR (International Public Sector Accounting Review), 2023)
This study aims to review the supervision of goods and services carried out by the Government's Internal Supervisory Apparatus (APIP) during the Covid-19 pandemic. This study uses a qualitative method using a scoping review approach. The data used in this study are laws and regulations, journal articles and online news using the keywords monitoring of government goods and services and the covid19 pandemic. This study concludes that the role of APIP in supervising state finances is urgently needed, one of which is through a Specific Purpose Audit. Audits for certain purposes aim to provide adequate assurance for the procurement of goods/services carried out following laws and regulations, which can be useful in meeting the needs for goods/services to accelerate the handling of Covid-19.